A trial of lopinavir-ritonavir in adults hospitalized with severe Covid-19 - Cao, B; Wang, Y; Wen, D; Liu, W; Wang, J; Fan, G; Ruan, L; Song, B; Cai, Y; Wei, M; Li, X; Xia, J; et al. (Massachusetts Medical Society, 2020)
Background No therapeutics have yet been proven effective for the treatment of severe illness caused by SARS-CoV-2.